2017
DOI: 10.1016/j.celrep.2017.02.016
|View full text |Cite
|
Sign up to set email alerts
|

miR-600 Acts as a Bimodal Switch that Regulates Breast Cancer Stem Cell Fate through WNT Signaling

Abstract: Breast cancer stem cells (bCSCs) have been implicated in tumor progression and therapeutic resistance; however, the molecular mechanisms that define this state are unclear. We have performed two microRNA (miRNA) gain- and loss-of-function screens to identify miRNAs that regulate the choice between bCSC self-renewal and differentiation. We find that micro-RNA (miR)-600 silencing results in bCSC expansion, while its overexpression reduces bCSC self-renewal, leading to decreased in vivo tumorigenicity. miR-600 ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 43 publications
2
75
0
Order By: Relevance
“…Additionally, four wells were left untreated to receive the DEAB control during the ALDEFLUOR assay (see below). Three days post-transfection, SUM159 cell amount and the %ALDH br cell amount (=%bCSC) upon gene knockdown were assessed using a previously described adaptation of ALDEFLUOR assay (Stem Cell technologies) for image acquisition and analysis in microplate format (El Helou et al, 2017). Briefly, after culture supernatant removal, 12 ll of an ALDEFLUOR/Hoechst mixture (13 ll of BAAA substrate per ml of ALDEFLUOR buffer + Hoechst 33342 [Sigma] at 25 lg/ml) was added in the culture wells.…”
Section: Cell Transfection and Miniaturized Aldefluor Assaymentioning
confidence: 99%
“…Additionally, four wells were left untreated to receive the DEAB control during the ALDEFLUOR assay (see below). Three days post-transfection, SUM159 cell amount and the %ALDH br cell amount (=%bCSC) upon gene knockdown were assessed using a previously described adaptation of ALDEFLUOR assay (Stem Cell technologies) for image acquisition and analysis in microplate format (El Helou et al, 2017). Briefly, after culture supernatant removal, 12 ll of an ALDEFLUOR/Hoechst mixture (13 ll of BAAA substrate per ml of ALDEFLUOR buffer + Hoechst 33342 [Sigma] at 25 lg/ml) was added in the culture wells.…”
Section: Cell Transfection and Miniaturized Aldefluor Assaymentioning
confidence: 99%
“…The last two miRViz networks connect miRNA nodes that share common mRNA targets 4 (Supplementary Note 3). As proof-of-concept, Supplementary Figure 3 compares two datasets and highlights a cluster of overexpressed miRNAs in pluripotent stem cells 5 , which are active in vitro to maintain the equilibrium of breast cancer stem cells 6 .…”
Section: Resultsmentioning
confidence: 99%
“…4 Using patientderived xenografts from primary breast tumors we demonstrated that miR-600 regulates tumor progression by controlling CSCfate. miR-600 silencing resulted in breast CSC expansion with an increase in tumor growth kinetic, whereas CSCs overexpressing miR-600 had a markedly reduced tumor-initiating capacity in recipient mice compared with control.…”
Section: Mir-600 Balances Breast Csc-fate Through Wnt Signalingmentioning
confidence: 98%
“…We developed a miniaturized ALDEFLUOR-probed CSC detection assay to perform high throughput screening. 4 We performed two concurrent miRNome-wide loss-and gain-of-function screens using locked nucleic acid and pre-miR libraries as miRNA inhibitors and mimics, respectively. We considered as a "hit" each miRNA that balanced the CSC/non-CSC ratio according to its expression level.…”
Section: Microrna Bimodal Switch For Csc-fate Decisionmentioning
confidence: 99%